Strategy for accelerating stunting prevention through religious approach to generate qualified generation - Noviansyah, Noviansyah; Romli, Khomsahrial; Mukmin, Hasan; Wijayanto, Reihana (International Journal of Public Health Science (IJPHS), 2022)
Stunting threatens qualified generation presence and greatly affects the success of a nation's development. The government has used many approaches to reduce the stunting except religious approach whereas in Indonesia as the majority Muslim country, many Indonesians are prone to follow religious leaders rather than a government official. The study obtained a strategy for accelerating stunting prevention through a religious approach. This analytic research used a qualitative approach with case study design. The participants in this research were 62 people namely advocacy, social support, and empowerment target in stunting prevention. The result showed that community empowerment in accelerating stunting prevention has not been optimally implemented. Even social support is adequate but Islamic religious counselors did not receive adequate information about stunting, so they did not optimally convey it back to the community. The policy for accelerating stunting prevention is adequate at the central, provincial, and district levels, however, the policies on religious approaches were limited. Strategy for accelerating stunting prevention through religious approach by using appropriate communication methods and channels such as pre-wedding counseling, Islamic study assemblies, and Friday sermons. Message structure or communication material on stunting prevention should become national policy.